The hidden curriculum and social preferences - Takahiro Ito; Kohei Kubota; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2015)
This paper examines the effects of school curricula on subsequent preference formation. The estimation results, using Japanese data, show that the actual curriculum at public elementary schools varies widely from area to area and is associated with preference formation. Specifically, pupils who have experienced participatory/cooperative learning practices are more likely to be altruistic, cooperative with others, reciprocal, and have national pride. In contrast, the influence of education emphasizing more on anti-competitive practices is negatively associated with these attributes. Such contrasts can also be seen for other preferences regarding government policies and a market economy. The findings imply that elementary school education, as a place for early socialization, plays an important role in the formation of life-long social preferences.
Keywords: D83; I21; Z13; 330; cultural transmission; socialization; preference formation; hidden curriculum; elementary education; Japan